The Influence of ESG on Operational Risk of Bank Issuers in Indonesia for the Period of 2019 – 2023 - Rizky Jati Mukti; Handi Handi; Kresna Nuswantoro; Jemitra Jemitra; Dewi Hanggraeni (Publikasi Indonesia, 2025)
This study investigates the relationship between environmental, social, and governance (ESG) scores and operational risk of banks in Indonesia. Using panel data from 17 bank issuers in Indonesia during the period 2019–2023 with a dynamic panel regression approach, the results showed that ESG scores did not have a significant influence on operational risk, although the coefficients showed indications of a negative relationship. These findings reflect the limited implementation of ESG in Indonesia's banking sector and the lack of uniform reporting standards and supporting infrastructure. In contrast, internal variables such as bank size (SIZE), profitability (ROA), and equity (ROE) show a significant relationship with operational risk. Bank size is negatively correlated with operational risk, while profitability shows a significant positive correlation. This study provides new insights into the importance of managing internal factors in mitigating operational risks, as well as highlighting the need to strengthen ESG regulations in Indonesia to improve the sustainability of the banking sector